Design with Fourth Nature. Issue 2 (3rd May 2020) - Bakshi, Anita; Gallagher, Frank
Abstract: This article posits designing with Fourth Nature as an alternative to dominant modes of practice in restoration ecology, heritage management and landscape architecture. We explore the contours of resistance in these fields to Fourth Nature landscapes, questioning how we might move past static and pure ideals while remaining in dialogue with the rich history of garden and landscape design. We explore why recent developments in the ecological sciences have not been more widely adopted in landscape architecture practices in the United States. Our approach questions long-held perceptions of appropriate plant assemblages and presents alternatives for managing eco-systems at historically layered landscapes where restoration of the historical reference is not practical or possible. We call for extending understandings of Fourth Nature into a framework for designed landscapes that goes beyond wildlands and spontaneous plants. This approach translates ecological values into a design language that is dynamic and process-oriented.